An additive long-range potential to correct for the charge-transfer failure of time-dependent density functional theory - Dreuw, Andreas; Plötner, Jürgen; Wormit, Michael; Head-Gordon, Martin; Dutoi, Anthony Dean (Zeitschrift für physikalische Chemie, 2010)
Time-dependent density functional theory is one of the most widely used methods for the calculation of excited states of large molecules. However, it exhibits substantial problems with charge-transfer excited states when conventional exchange-correlation functionals are employed. Here, we introduce an additive long-range potential that can, in principle, be directly employed with any existing local, GGA or hybrid-functional, without re-fitting of the original functionals. The additive potential shifts the excitation energies to higher values and corrects for the wrong asymptotic behavior of their potential energy surfaces with respect to charge-separating coordinates. First examples of its successful application are shown.